Upaya Meningkatkan Keterampilan Motorik Halus Anak Usia Dini Melalui Usap Abur - Irfadillah Putri; Masrul Masrul; Musnar Indra Daulay (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study is motivated by the low level of fine motor skills in group B children at Garuda 005 Sawah Kindergarten, fine motor skills are fine movements involving certain parts that are carried out by small muscles and wiping is the guidance of drawing activities through a touch of color and artistry of shape. The purpose of the study was to determine the effect of smudging activities on children's fine motor skills. The method used in this research is Classroom Action Research (PTK). This study amounted to 18 children consisting of 9 boys 9 girls. The instrument used is an observation sheet that is adjusted to the indicators. Data collection techniques used observation and documentation. Data analysis is calculating data to verify and interpret with the formula P = F / N X 100%. The percentage results increased starting from pre-study, cycle I and cycle II, it can be said that the ability of fine motoriuk in children's wiping activities has reached the criteria for success, namely reaching 88.9% which is said by researchers and teachers to be successful.